2019
DOI: 10.3390/w11112242
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Sources for Precipitation and Hydrograph Components of the Sutri Dhaka Glacier Basin, Western Himalayas

Abstract: Himalayan glaciers are the major source of fresh water supply to the Himalayan Rivers, which support the livelihoods of more than a billion people living in the downstream region. However, in the face of recent climate change, these glaciers might be vulnerable, and thereby become a serious threat to the future fresh water reserve. Therefore, special attention is required in terms of understanding moisture sources for precipitation over the Himalayan glaciers and the hydrograph components of streams and rivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Moisture source for precipitation over the study region is dominantly (>70%) derived from the Mediterranean regions by western disturbances (WDs) during winter and early spring, with minor (<20%) contributions from the Indian Summer Monsoon (ISM) during the summer monsoon season (June-September). A three-component hydrograph separation based on oxygen isotope fingerprinting and field-based ablation measurements for one of the glacier basin (Sutri Dhaka) revealed that glacier ice melting is the dominant (65-80%) contributor to the river water, followed by snow melt (20-35%) (Singh et al 2019). Spatial mass balance gradient varied with specific glacier's location and topography.…”
Section: Implications Of Climate Change For Himalayan Snow and Glaciementioning
confidence: 99%
“…Moisture source for precipitation over the study region is dominantly (>70%) derived from the Mediterranean regions by western disturbances (WDs) during winter and early spring, with minor (<20%) contributions from the Indian Summer Monsoon (ISM) during the summer monsoon season (June-September). A three-component hydrograph separation based on oxygen isotope fingerprinting and field-based ablation measurements for one of the glacier basin (Sutri Dhaka) revealed that glacier ice melting is the dominant (65-80%) contributor to the river water, followed by snow melt (20-35%) (Singh et al 2019). Spatial mass balance gradient varied with specific glacier's location and topography.…”
Section: Implications Of Climate Change For Himalayan Snow and Glaciementioning
confidence: 99%
“…At one end, this elevated topography of the Himalayas limits the northward transport of moisture‐laden summer monsoon winds, while on other end it restricts the entry of winter icy winds coming from the north (Ali et al, 2020). Moisture sources of precipitation over the eastern and central Himalayas are primarily driven by ISM during June to September, while moisture sources over the western Himalayas are predominantly derived by WDs from October to May (Singh et al, 2019; Jeelani and Deshpande, 2017; Madhura et al, 2015). The continuous transportation of WD and ISM moistures over the region (Dimri et al, 2004) is primarily responsible for regulating seasonal and perennial flows in rivers and groundwater (Lone et al, 2021; Jeelani et al, 2018, 2017a,b,d; Kumar et al, 2010; Anders et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the scarcity of ice core records from the Indian Himalaya makes it difficult to understand the role of precipitation and temperature in the Quaternary glaciations. Since the d-excess values reflect westerly precipitation during winters in the Western Himalaya 16 , reconstruction of moisture sources during the Holocene from sediment records provides a new avenue for understanding past climate and glacier variability in the Himalaya. Reconstruction of dynamics of moisture changes during the Holocene is of great importance for societal development (e.g., Indus civilization) and future climate changes.…”
Section: Introductionmentioning
confidence: 99%
“…The d-excess values of > 17‰ from Sutri Dhaka glacier in the nearby area, reveal the sources of moisture from the Mediterranean region 16 .The deuterium excess (d-excess) is a climatic independent indicator to track the source of moisture and is defined as d (‰) ≡ δD − 8.δ 18 O 19 and controlled by wind speed, relative humidity and temperature from the moisture-generating reservoir 20 , 21 . The d-excess is used to delineate the source of precipitation and its low values during the ISM reflect moisture transport from the Indian Ocean 16 , 22 whereas high values show moisture from the Westerly precipitation 16 , 23 .Therefore, we have used the same d-excess value to trace the origin of moisture source either from the ISM or the Westerlies. Located at the junction of the Westerlies and ISM, the Chandratal receives sediment through catchment erosion, weathering, and windblown dust.…”
Section: Introductionmentioning
confidence: 99%